The Influence of Leadership and Work Environment on Employee Work Morale at the East Kutai Regional Secretariat - Udau, Sovia; Prakoso, Cathas Teguh; Rande, Santi (Dinasti Research, 2026)
This study adopts an explanatory design aimed at examining how leadership and workplace conditions affect outcomes on employee morale at the Regional Secretariat of East Kutai Regency. This study analyzes the Independent variable of leadership (X1) with indicators of Guiding, Building and motivating, Driving the organization, Establishing good communication. The work environment variable (X2) with indicators of Facilities and Infrastructure, Work Relations, Tranquility, Lighting and Cleanliness and the Dependent variable of Work Morale (Y) with indicators of absenteeism, cooperation, job satisfaction and discipline. Data analysis used is Data were analyzed through association testing, explanatory power assessment, and linear modeling via SEM-PLS morale with a p value of 0.000 <0.05, T statistic 10.486 > 1.96 and a positive path coefficient of 0.576. The direction of the positive influence indicates that the better the leadership, the better the employee's work morale will be. And workplace conditions significantly affect employee enthusiasm as indicated by statistical testing of 0.000 <0.05, T statistic 7.640 > 1.96 and a positive path coefficient of 0.450. The direction of this positive influence indicates improvements in workplace quality lead to higher employee motivation.